2006
DOI: 10.1002/fuce.200600034
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Stable Ionomers and Ionomer Membranes for Fuel Cells

Abstract: Membranes based on sulfonated arylene polymers and their cross‐linked blends were prepared. Embedding the ionomers into textile or porous PTFE matrix and/or doping with ZrP nanoparticles reduced the swelling, and improved the thermal stability. PTFE reinforcement led to an excellent single cell performance, which is promising for PEMFC applications. Some of the membranes performed better than Nafion®. The net methanol crossover correlates with the membrane thickness and composition, but surprisingly, suppressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…, and comparing the coupling constants with literature values [15], it was concluded that the observed spectrum consists of five different, simultaneously appearing radical species with identical g values ( Table 3; details are reported in [20]). The fractions which are determined by matching the intensities in the simulation are 26% for radical 6, 14% for radical 7, 35% for radical 8, 17% for radical 9, and 8% for radical 10.…”
mentioning
confidence: 97%
“…, and comparing the coupling constants with literature values [15], it was concluded that the observed spectrum consists of five different, simultaneously appearing radical species with identical g values ( Table 3; details are reported in [20]). The fractions which are determined by matching the intensities in the simulation are 26% for radical 6, 14% for radical 7, 35% for radical 8, 17% for radical 9, and 8% for radical 10.…”
mentioning
confidence: 97%
“…[77][78][79] The results suggested that mechanical strength and thermal stability were improved to some degree. However, sufficient proton conductivity is still an important concern for cross-linked membranes with high mechanical and thermal stability.…”
Section: à2mentioning
confidence: 90%
“…Jiang et al, 2006a;Kuan et al, 2006; H.K. Mitov et al, 2006;Yang et al, 2001aYang et al, ,2001bYang et al, ,2004, SPEEK (Bonnet et al, 2000;Nunes et al, 2002;Silva et al, 2005b;Tchicaya-Bouckary et al, 2002;Triphathi et al, 2007Triphathi et al, ,2009, SPEK (Nunes et al, 2002;Ruffmann et al, 2003) and difulfonated poly(arulene ether sulfone) (Hill et al, 2006). A similar inorganic material derived from ZrP, named zirconium phosphate sulfophenylen-phophonate was also used as a filler with Nafion ® (Y.T.…”
Section: Organic/zirconium Phosphate Nanocomposite Membranesmentioning
confidence: 99%